Assessment of Ergonomic Risk Factors among Metal Sculpture Workers and Future Scope of AI Applications in Ergonomic Evaluation - Mishra, Yogesh; Singh, Ashish K.; Meena, Makkhan Lal; Dangayach, Govind Sharan (Recent Patents on Engineering, 2024)
Background: Handicraft workers usually carry out daily activities by adopting awkward postures. The most prevailing health issues among handicraft workers are musculoskeletal disorders (MSDs). Objective: The current research aims to assess the occurrence of musculoskeletal symptoms and investigate risk factors associated with musculoskeletal disorders among metal sculpture artisans. Subsequently, the study highlighted the future scope of AI applications in ergonomic evaluation. Methods: 144 male metal sculpture workers participated in the study. A modified Nordic questionnaire was adopted to determine the musculoskeletal problems among metal sculpture workers. The probable risk elements for MSD symptoms were identified by applying binary logistic regression. Results: Most workers faced discomfort in various body parts, particularly the wrist, lower back, and shoulders. The outcome of the logistic regression model revealed that job-related factors have significantly contributed to the development of MSD symptoms. Conclusion: This study concedes that awkward working postures for prolonged periods highly affect the health of metal sculpture workers, and there is a need for ergonomic intervention to minimize the risks of musculoskeletal disorders. The study also emphasizes the future scope of Artificial Intelligence (AI) applications that can be used in ergonomically assessing working postures.
Keywords: musculoskeletal disorders